2018
DOI: 10.1080/10962247.2018.1496189
|View full text |Cite
|
Sign up to set email alerts
|

Integrating site-specific dispersion modeling into life cycle assessment, with a focus on inhalation risks in chemical production

Abstract: It has become increasingly important for environmental managers to evaluate the human health (HH) impact of chemicals in their supply chain. Current life cycle assessment (LCA) methods are limited because they often only address the HH impact at large geographical scales. This paper aims to develop a method that derives a regionalized life cycle inventory data set and site-specific air dispersion modeling to evaluate the HH impact of chemicals along the life cycle phases at finer geographical scales to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Moreover, there is the possibility of partial chemical degradation to unknown products with similar or different toxicity from the parent contaminant. In response to these challenges, the bottom-up approach has been used in risk assessments for complex mixtures (Tian and Bilec 2018). A variation of this approach was taken in this study, namely to use the observed toxic effects pattern in an animal model to identify contaminants of potential concern rather than predicting effects based on chemical composition (Xia et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is the possibility of partial chemical degradation to unknown products with similar or different toxicity from the parent contaminant. In response to these challenges, the bottom-up approach has been used in risk assessments for complex mixtures (Tian and Bilec 2018). A variation of this approach was taken in this study, namely to use the observed toxic effects pattern in an animal model to identify contaminants of potential concern rather than predicting effects based on chemical composition (Xia et al 2019).…”
Section: Introductionmentioning
confidence: 99%